The City and its Waste. Notes for Reconfiguring the Concept of Heterotopia (Andamios, Revista de Investigación Social, 2015)
This paper aims to characterize, for the social-ensemble that negatively defines them, the marginal urban spaces stigmatized in terms of their structuring value. We state that these spaces must be understood according to the system they integrate with pure and neutral spaces. Based on an critical review of the concept of heterotopy, we state that these sites of insignificant relative weight, in the material and political economy of contemporary cities, become essential for their symbolic and affective economy. These spaces accomplish the socially effective —and humanly cruel— task of setting the lower limits of the urbanensemble, which takes consistency by their sustained expulsion. By embodying the radical exterior of contemporary cities, these spaces also act as the cathartic and projective locus of the collective imagination and passions that, at the same time, feed from them and discharge against them.
Keywords: Heterotopia; urban space; waste; sacred